Health Literacy and Strengthening Mental Resilience in Immigrant Youth (Turkey Health Literacy Journal, 2020)
Nowadays, there is an intense wave of immigration in the world and Turkey. The density of the young population is also very high in these migration. The young immigrants have many areas of need such as health, education and social areas in the country they migrate to. Due to these problems, the need for support and expectations of young people affects their mental health significantly. In the context of mental health, psychological resilience is of special importance for primary protection. In order to be able to successfully overcome the adverse conditions faced by immigrant youth despite very difficult conditions and to adapt to the environment and society they live in, their psychological strength must be strengthened. In this process, increasing the level of health literacy, which provides the ability to recognize the health system and establish health communication correctly, will also strengthen the adaptation. The multi-sectoral activities of determining, increasing and enhancing the level of health literacy of young immigrants will increase the applicability and sustainability of the programs.